Global Media Narratives and Nepal’s International Image - Adhikari, Yuba Raj (NCWA Annual Journal, 2026)
In the contemporary global communication environment, international media play a significant role in shaping how countries are perceived beyond their borders. For smaller and developing states such as Nepal, whose global visibility is often episodic and event-driven, international image formation is heavily influenced by external media narratives. Countries in the Global South face geopolitical risks that shape their international image through narratives that follow a pattern of selective external definition. Narratives about Nepal that attract international attention lack the detailed information needed to produce a proper understanding of its identity. This article examines how global media portrayals shape Nepal’s international image. It argues that Nepal is frequently represented through selective frames that focus on natural disasters, political instability, climate vulnerability, heritage tourism, and its geopolitical positioning between India and China. While these portrayals are grounded in factual realities, they often present a partial and crisis-oriented perspective that obscures Nepal’s political agency, institutional development, and socio-economic transformation. The article highlights the structural dynamics shaping Nepal’s generated visibility and discusses their implications for public diplomacy, soft power, tourism, and foreign investment by analysing historical and contemporary representations. The article concludes that Nepal must adopt more proactive and strategic communication efforts to promote a balanced, multidimensional international image that reflects both its challenges and its resilience.